Premature Ovarian Insufficiency: A Review - Avantika Gupta; Purnima Tiwari; Chetan Khare (European Medical Journal, 2019)
Premature ovarian insufficiency is waning of ovarian function before the age of 40 years. This hypoestrogenic state is characterised by menstrual irregularities and loss of fertility in the patient. This review narrates evaluation, consequences, and management of this complex entity. Truncation in ovarian physiology at such an early age renders the patient prone for various short- and long-term health consequences which negatively affect physical and psychological well-being of the patients. Therefore, this review emphasises that timely initiation of hormonal therapy is mandatory to mitigate the distressing menopausal and/or other hypoestrogenic symptoms to improve the quality of life of such patients. Although much has been said about premature ovarian insufficiency, many aspects of this condition still need to be explored in order to identify this population subgroup before happening of the catastrophic event and to formulate strategies and interventions to delay the premature cessation of ovarian functions.